Editorial: Institutional, economic and demographic transition and its impact on the transport system - Lanzendorf, Martin; Gather, Matthias (European Journal of Transport and Infrastructure Research, 2005)
During the last 15 years most central and east european countries faced an era of institutional, economic and demographic transition. With the fall of the wall and the end of the Soviet Union, the former socialist countries transformed their political, economic and social institutions; today, some of them are already a member state of the European Union. The re- unificated Germany was not only affected by this process in its eastern part, the former German Democratic Republic (GDR), where the political and institutional structures were entirely exchanged; with the end of the “Rheinische Bundesrepublik”, the incarnation of a welfare and growth oriented Fordist society, also former West Germany had to adapt to this transition and still is facing a process of institutional modernisation.